The Textbook “Rita, Raitis and Numbers” by J. Mencis (Sen.) and D. Draviņa for the Pre-school Learners - Drelinga, Elga; Iliško, Dzintra; Zariņa, Sandra (Pedagogika, 2015)
The article presents the analyses of the textbook for the primary school children in math “Rita, Raitis and numbers” designed by J. Mencis (Sen.) and D. Draviņa who emphasize the importance of developing basic math notions for the primary school children as seen in the context of sustainable education. This is essential to recognize the importance of teaching basics that need to be developed at the primary stage of education in preparing children for school. The aim of the study is to offer a detailed study of methods offered by J. Mencis (Sen.) and D. Draviņa for pre-school children and its applicability nowadays. The authors offer suggestions about the most efficient approaches in teaching math for the primary school children. The book designed in 90’s is still efficient today. Therefore, the authors present a detailed analysis of the methods and contents of the school subject suggested by the scientist J. Mencis for the contemporary purposes in preparing children for schools. The authors have used a content analysis to study how the interests and the needs of girls and boys are being met in stories, revealed in the content of exercises and in the choice of hand-outs. Particular attention in this study has been paid to a representation of the role of family in preparing children for school, as well as to a gender dimension in the textbook. The main research problem is to reveal the suitability of the textbook for the purposes of a contemporary pupil. The aim of the study is to prove that the contribution of J. Mencis (Sen.) and D. Draviņa in teaching math is of national value and how it corresponds to the criteria of a contemporary textbook. The objectives of the study is to 1) explore gender portrayal in the book, 2) its suitability of us by the families in training the child for the schools, as well as 3) the plot of the textbook and it’s suitability for children. The book has been used by several generations of teachers, it corresponds to the criteria required for the contemporary textbook in math, and can serve as bases for further use.